It's All in the Plan: A Document Analysis of Victorian Council and Public Library Disability Access and Inclusion Plans. Issue 1 (2nd January 2020) - Muir, Rebecca; Carroll, Mary
ABSTRACT: The Victorian Government requires councils to create a disability action plan or discuss inclusion in their council plan. Disability action plans aim to reduce barriers in accessing goods, services or facilities and to reduce discrimination. With public libraries in Victoria being managed by councils either individually or in a corporation, these action plans have the potential to directly impact on the community via library services. Using qualitative and quantitative document analysis, a total of 31 Victorian councils or library corporation disability action plans were analysed to understand what these plans saw as the action areas for libraries working with people with a disability. It was found that definitions of disability in these action plans broadly matched with the wider disability and libraries literature, with most councils in Victoria having an online action plan but comparatively few library corporations having the same. Libraries were largely discussed in relation to six theme areas (Access; Certification; Collections; Programming; Technology; and Training). An overall summary indicates that libraries involvement in council disability action plans is less detailed than in some library corporation action plans.